CCDC58 drives lung adenocarcinoma progression via the PI3K/AKT signaling pathway - Dai, Wenchao; Yang, Jun; Yang, Wenming; Zhang, Guibin; Chen, Hang; Ren, Bi; Dang, Xin; Xue, Linfeng; Jiang, Li (Frontiers in Oncology, 2025)
BackgroundPrevious studies have implicated Coiled-coil domain-containing 58 (CCDC58) in the malignant progression of hepatocellular carcinoma and breast cancer. However, its role in lung adenocarcinoma (LUAD) remains poorly understood.MethodsBioinformatics analysis was employed to examine CCDC58 expression patterns in LUAD and their correlation with clinical features. We validated CCDC58 expression levels using quantitative real-time PCR (qPCR), Western Blot (WB), and immunohistochemistry staining (IHC). Furthermore, we assessed the impact of CCDC58 knockdown on LUAD cell behavior using proliferation assays, cell migration assays, wound healing assays, and flow cytometry. We explored the effects of CCDC58 knockdown on apoptotic proteins, epithelial-mesenchymal transition (EMT) markers, and PI3K/AKT signaling pathway components through WB. Finally, we evaluated the role of CCDC58 in tumor growth in vivo using a nude mouse xenograft model, with subsequent IHC analysis of tumor tissues.ResultsCCDC58 showed significant upregulation in LUAD cell lines and clinical specimens, leading to poor prognosis. CCDC58 expression was identified significant correlation with tumor microenvironment. In vitro, suppressing CCDC58 expression significantly impaired the capacity of growth and migration of LUAD cells. CCDC58 knockdown inhibited EMT, promoted apoptosis, and induced G1- phase cell cycle arrest. Significantly, CCDC58 knockdown inhibited the activity of the PI3K/AKT signaling pathway. In vivo, CCDC58 knockdown suppressed tumor growth and enhanced apoptosis.ConclusionsAbove all, this study reveals that CCDC58 plays multiple pro-tumorigenic roles in the progression of LUAD. These results enhance the understanding of LUAD pathogenesis and highlight CCDC58 as a potential therapeutic target and prognostic biomarker.